Multivariate analysis of some important quantitative traits in rapeseed (Brassica napus) advanced lines (Journal of Oilseed Brassica, 2026)
Development of new rapeseed (Brassica napus L.) cultivars requires efficient tools to monitor traits relationship in a breeding program. Twenty four rapeseed genotypes including 2 cultivars and 22 advanced lines were evaluated based on randomized complete block design with three replications. Significant genotypes effects were exhibited for phenological traits, plant height, yield components and seed yield, indicating significant genetic differences among the genotypes. High broad sense heritability were estimated for phenological traits, pods on main axis and seed yield signifying selection gain for improving these traits will be high. Duration of flowering and pods on main axis had high value of genetic coefficient of variation. The results of factor analysis exhibited four factors including sink factor (pod per plant, pods length and seed yield), fixed capital factor (phenological traits), secondary fixed capital factor (duration of flowering) and metric factor (plant height). The results of stepwise regression analysis revealed that plant height and pods per plant had more decreasing and increasing effects on seed yield, respectively. On the basis of cluster analysis, the genotypes were classified in four groups and the group with high seed yield had high mean value of pods per plant.